Political economy and fiscal policy - Brentano, Lujo, 1844-1931.; Cobden Club (London, England) (London, New York [etc.] Cassell and Company, Ltd., 1910)
This book is on political economy and fiscal policy. It highlights the hopeless condition of our finances and how it can be sustained by under studying a foreign country.
Cobden Club stamp on t.-p.
nmn 09/07/13
Loans
Keywords: Tariff -- Germany; Germany -- Commercial policy; Tariff -- Great Britain; Great Britain -- Commercial policy